Why do companies cook the books? Empirical study of the motives of creative accounting of Slovak companies - Jakub Michulek; Lubica Gajanova; Anna Križanová; Roman Blazek (Administrative Sciences, 2024)
Studies on creative accounting date back to the latter part of the 20th century. Creative accounting is still a big challenge in financial accounting. The problem of financial statement manipulation might be investigated, for instance, from an accounting, legal, ethical, or psychological perspective. This research aims to identify the main motives for the use of creative accounting and to find out whether corporate culture has an impact on the motives leading to the use of creative accounting. Data collection took place from 18 November 2023 to 18 December 2022. In the research, we used Pearson's χ2 test to determine the dependence of the studied variables in contingency tables. Subsequently, correspondence analysis was used. The type of corporate culture does not have an impact on the motives that lead to creative accounting. It was proven that the type of corporate culture has an impact on the performance of creative accounting actions based on the request of a senior employee. The uniqueness of the research lies in the investigation of creative accounting from a psychological and managerial point of view in the territory of the Slovak Republic.
Keywords: 350; corporate culture; creative accounting; employee behavior; motives of creative accounting; sustainable development